Implementation of the Plan Maintenance System (PMS) Function on Lifeboats to Support Sailing Safety on the Jambo VIII Ferry Motor Ship - Salsabila Putri Naftali; Dety Sutralinda; Romanda Annas Amrullah; Anak Agung Istri Sri Wahyuni (International Journal of Science and Environment (IJSE), 2026)
Sailing safety on passenger ships such as KMP Jambo VIII is often threatened by lifeboat failure due to suboptimal maintenance, even though the Plan Maintenance System (PMS) has been implemented. This study aims to analyze the implementation of the PMS function on lifeboats and identify its obstacles to supporting sailing safety. This type of qualitative descriptive research was conducted on the KMP Jambo VIII crew population with a purposive sample of 4 key informants (Captain, Chief Officer, Pumpman, Boatswain). The main research instruments were supported by semi-structured interview guidelines, observation sheets, and documentation; data analysis used the Miles and Huberman model (reduction, presentation, conclusion). The results show that the PMS runs through tiered inspections despite being hampered by a busy operational schedule, scarcity of spare parts, and administrative-field gaps. The conclusion recommends regular crew training and PMS digitalization for safety optimization.